R&D in Traditional Color-lint Cottons of Andhra Pradesh, India - Ravindranath, K.; Reddy, Pocha Brahmananda (International Journal of Bio-resource and Stress Management, 2010)
Colored cottons Coconadas-1 and Coconadas-2 of G. arboreum group (desi) were grown on a commercial scale in Guntur and Nandyal areas of Andhra Pradesh. These are eco-friendly and free from health hazards. These colored cottons were replaced with white linted types due to their poor yielding ability, poor fiber quality and non-stability of the natural color. Further the introduction of artificial dyes of different colors, the colored cottons lost its importance to white linted types. Further research on improvement of colored cottons initiated at Regional Agricultural Research Station, Nandyal has resulted in isolation of few varieties NDL HC-1, HC-2 and BS 1000 at Bharathi Seeds R&D unit, Nandyal belonged to Hirsutum group and NDL AC-1 and AC-2 in G. arboreum (desi) group. Among these, BS-1000 (G. hirsutum) has recorded 28% increase in yield over white linted cotton variety Narasimha (check). This denotes the possibility of developing a superior colored type with higher yield and better fiber characters which facilitate the manufacture of eco-friendly garments to catch up foreign markets, and thereby improve country’s economy benefiting the farmers.